Comprehensive Sexuality Education for Addressing Young People’s SRHR Status in Nepal - Aryal, Bhagawan; Adhikari, Anup; Pokhrel, Romkanta (Interdisciplinary Research in Education, 2023)
This article reflects the narrative evaluation in the domain of young people's SRHR status and need for CSE. Young people in Nepal are particularly at risk for early marriage and childbearing, as well as other SRHR-related issues. CSE is recommended as a suitable technique to deal with these concerns affecting young people. CSE is a rights-based approach to teaching the cognitive, emotional, physical, and social aspects of sexuality. It helps young adolescents develop the knowledge, ideas, and beliefs they need to choose and embrace their sexuality in intimate relationships on a physical and emotional level. Its promotion is proposed as a solution to assist Nepalese young in enhancing their SRHR status.